SIMULATION STUDY AND STRENGTH VALIDATION OF PLANES’LOAD AT DIFFERENT POSITIONS OF COAL PLOUGH - ZHAO LiJuan; CHEN Lei; TIAN Zhen (Jixie qiangdu)
Planes are the execution tools of coal plough,the work load directly affecting the planing capacity and production efficiency of the plow. In order to study the load characteristics,developing the coal plow load calculation program based on Matlab and VC,which can calculate the random load of planer at different positions according to the different simulating coal seam occurrence conditions; Planes at different positions were simulated and the strength verified based on ADAMS software. By analyzing the results indicate that : in the same cutting depth,the loads of planes at the different positions are random,in which load short broadsword’s means and standard deviations of the three load are minimum and the cutter force is relatively stable and uniform compared with other positions,followed by long broadsword,knife top and bottom knife; With increasing of planing depth,three forces of planes suffered have varying degrees increased,When the cutting depth exceeds a certain value,cutting resistance will be significantly increased; when the cutter spacing exceeds a certain transversal distance,cutting force increases sharply; In the working process,long and short waist by the maximum stresses are located in knife body thickness position transition connection and the knife body and the lamellar alloy head is embedded,main failure mode for the wear and fracture;the top and bottom knife knife connected with the knife base part chamfer can relax the stress concentration. Analysis results of load planer reliability and structure optimization design provides a theoretical basis for the study of dynamic.